The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1212/01.wnl.0000310981.44676.de
|View full text |Cite
|
Sign up to set email alerts
|

Bone health in young women with epilepsy after one year of antiepileptic drug monotherapy

Abstract: Objective-Antiepileptic drugs (AEDs) may have adverse effects on bone mineral density (BMD) and metabolism. We previously reported biochemical evidence of increased bone turnover in pre-menopausal women with epilepsy on phenytoin monotherapy compared with those on carbamazepine, lamotrigine, and valproate. We therefore hypothesized that rates of bone loss would be higher in young women treated with phenytoin.Methods-Ninety-three premenopausal women with epilepsy receiving a single AED (carbamazepine, lamotrigi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
3
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(118 citation statements)
references
References 24 publications
6
102
3
7
Order By: Relevance
“…26) In support of this hypothesis, several clinical studies have reported the elevation of serum PTH levels 27) and the reduction of serum 25(OH) D levels in patients treated with enzyme-inducing AEDs. 28) In contrast to this finding, several studies have observed no significant differences in these parameters. 29,30) In this study, we investigated the effect of AEDs on vitamin D metabolism, and found no significant difference in serum calcium, 25(OH) D, and PTH levels between the control group and the AED-treated groups.…”
Section: Discussionmentioning
confidence: 78%
“…26) In support of this hypothesis, several clinical studies have reported the elevation of serum PTH levels 27) and the reduction of serum 25(OH) D levels in patients treated with enzyme-inducing AEDs. 28) In contrast to this finding, several studies have observed no significant differences in these parameters. 29,30) In this study, we investigated the effect of AEDs on vitamin D metabolism, and found no significant difference in serum calcium, 25(OH) D, and PTH levels between the control group and the AED-treated groups.…”
Section: Discussionmentioning
confidence: 78%
“…Cytochrome-inducing AEDs are known to affect bone mineral density and are associated with bone disorders such as osteoporosis and fractures during and after menopause. Phenytoin has been found to be associated with decreased levels of bone-specific alkaline phosphatase, as well as increased bone turnover, which can predispose to fractures, especially to the neck of femur (Pack et al, 2008). Finally, topiramate use is associated with low parathyroid hormone levels and increased bone turnover in premenopausal women (Heo et al, 2011).…”
Section: Menopause-related Issuesmentioning
confidence: 99%
“…Pack and colleagues (11) followed women on AED monotherapy with PHT, CBZ, LTG or VPA for a year. They found significant loss of bone at the femoral neck in PHT-treated patients; they also found that reductions in 25-OHD were associated with increases in bone turnover markers, all of which is consistent with the aforementioned prevailing hypothesis.…”
Section: Bone and Vitamin D Metabolismmentioning
confidence: 99%